An Approximate Method for Calculating the Distance Between Regular Languages for Multitape Finite Automata - Grigoryan, Tigran A. (Mathematical Problems of Computer Science, 2021)
Sets of word tuples, accepted by multitape finite automata and a metric space for languages accepted by these automata, are considered. These languages are represented using the same notation as the known notation of regular expressions for languages accepted by one-tape automata. The only difference is the interpretation of the ”concatenation” operation in the notation. An algorithm is proposed for calculating the introduced distance between regular languages accepted by multitape finite automata.